Evaluación financiera en la Cooperativa de Ahorro y Crédito “El Cafetal” durante el periodo 2019 – 2020. - Arciniegas González, Diego Anthony (2022)
How can you determine that a cooperative is doing well economically? How can you determine if its items fluctuated positively or negatively? The truth is that you cannot guess or invent numbers to find out. The fastest and most reliable way to find out would be to carry out a financial analysis. The main objective of this case study is to evaluate the financial situation of the El Cafetal Savings and Credit Cooperative, it is intended to achieve a peripheral view of the accounts and determine how the oscillation of its items affects or benefits the cooperative. The documentary methodology will be used for the compilation of the necessary documents to carry out the financial analysis, the analytical method that starts under the concept of effect and cause will also be used and thus determine what effect the change of values in a cooperative would have within the cooperative. account from one economic period to another and what would cause said change in the cooperative and the deductive methodology because it frames a whole and returns it in specific and understandable concepts.